2007
DOI: 10.1111/j.1348-0421.2007.tb04000.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Comparison of the Pharmacodynamics of Four Antifungal Drugs in a Mouse Model of Disseminated Candidiasis Using Microbiological Assays of Serum Drug Concentrations

Abstract: The aim of this study was to compare the pharmacodynamics of the azole antifungal drugs fluconazole, itraconazole and ketoconazole, and the polyene antifungal amphotericin B, in a mouse model of disseminated Candida albicans infection. In order to directly compare effective serum concentrations of these antifungals, drug concentrations were assayed microbiologically by measuring inhibition of C. albicans mycelial growth (mMIC) in a mouse serum‐based assay (serum antifungal titer). Efficacy in the mouse infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…FCZ. The dose of FCZ used in the present study was determined on the basis of a literature search 19 and preliminary experiments. We found that 0.5 mg/kg FCZ approximated the ED 50 of FCZ and was able to protect fungusinfected mice and prolong their survival.…”
Section: Survival Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…FCZ. The dose of FCZ used in the present study was determined on the basis of a literature search 19 and preliminary experiments. We found that 0.5 mg/kg FCZ approximated the ED 50 of FCZ and was able to protect fungusinfected mice and prolong their survival.…”
Section: Survival Analysismentioning
confidence: 99%
“…assay is the most commonly used method to investigate infection with C. albicans. [19][20][21][22][23][24] Briefly, fungal cells were prepared and injected as described above for the mouse model of systemic candidiasis. Drug treatments were given to 10 different groups (n ¼ 5 mice in each group) for 7 consecutive days with once daily injections.…”
Section: Survival Analysismentioning
confidence: 99%
“…These dose-based investigations were used to indicate the optimal clinical dose regimen for improving efficacy and for prediction of the clinical outcome against susceptible and resistant pathogens (Lee et al 2000; Pai et al 2007; Clancy et al 2005). Although these MIC data contributed to progress in antifungal therapy, the values do not correspond to the in vivo effective concentrations (Maki et al 2007, 2008) and accurate pharmacodynamic parameters, such as the time to reach an effective concentration in vivo could not be determined. Furthermore, there are no criteria for determining sub-MIC values using such methods, and the sub-MIC effect cannot be discriminated from the post-antifungal effect (PAFE).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the use of an ex vivo (mouse serum) assay of mycelial growth (Maki et al 2006) can be applied to enable direct comparison of the serum concentrations of azoles and the polyene, amphotericin B (Maki et al 2007) and the in vivo efficacy of echinocandins (Maki et al 2008) in a mouse model of infection. The use of undiluted serum is important because the bloodstream environment determines most in vivo protein binding of drugs (Hage et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation